Art and practice of managing projects - Hamilton, Albert (Thomas Telford, 2010)
This title brings together over 40 years of experience and research from industry leader Albert Hamilton. With advice that is easy to interpret and apply to your projects, this internationally relevant book provides the tools and techniques you need to increase effectiveness at all levels of your project team and to achieve your strategic goals.